A non- conference review: a note on conferences that never were, those that may be and those that will be in 2021. Issue 2 (4th May 2019) - Azara, Iride
ABSTRACT: A non-traditional conference review offering a synthetic update on the latest academic and industry conference developments in the areas of wellness and wellbeing as well as some thoughts on what future conferences may look like in the near and long term future.